McCormick and Carey families papers - Carey, William H., 1841-1863.; McCormick, William, 1834-1863.
Correspondence from and about William McCormick of the 16th Ohio Infantry Regiment and William H. Carey of the 120th Ohio Infantry Regiment relating primarily to their Civil War service prior to and during the Vicksburg campaign of 1863. Also includes letters from other soldiers to Carey's sister, Rachel B. Carey; a letter (Dec. 1883) to Martha Matilda (Mrs. J.B.) McCormick describing missionary activities in Micronesia; and an 1861 valedictory address by William H. Carey, his obituary, and a poem written in his memory.
McCormick and Carey families of Wayne County, Ohio.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Carey, Rachel B. -- Correspondence; McCormick, Martha Matilda, -- 1858-1925 -- Correspondence; Carey family; McCormick family; Missions -- Micronesia; United States. -- Army. -- Ohio Infantry Regiment, 16th (1861-1864); United States. -- Army. -- Ohio Infantry Regiment, 120th (1862-1865); Mississippi -- History -- Civil War, 1861-1865 -- Campaigns; Ohio -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Vicksburg (Miss.) -- History -- Siege, 1863.